CMV-encoded Fcγ receptors: modulators at the interface of innate and adaptive immunity - Corrales Aguilar, Eugenia (2014)
The constant region of IgG antibodies mediates antiviral activities upon engaging host Fcγ receptors (FcγRs) expressed by a variety of immune cells, such as antibody-dependent cellullar cytotoxcity (ADCC) executed by natural killer (NK)cells. Human cytomegalovirus (HCMV) is unique among viruses by encoding also an array of several Fcγ-binding glycoproteins with cell surface disposition and concomitant incorporation into the virion. Evidence is increasing that the virus-encoded Fcγ receptors differ in their Fcγ binding mode but effectively operate as adversaries of host FcγRs since they are able to prevent IgG-mediated triggering of activating host FcγRs, i.e., FcγRI, FcγRIIA, and FcγRIIIA. Here we discuss virus-encoded FcγRs as the first known HCMV inhibitors of IgG-mediated immunity which could account for the limited efficacy of HCMV hyperimmune globulin in clinical settings. A better understanding of their molecular mode of action opens up new perspectives for improving IgG therapies against HCMV disease.